(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Burns are a global public health problem and it is one of the most common emergencies admitted to the hospitals. This is retrospective study which included 60 cases of deaths due to burns which were autopsied between June 2015 to March 2017 at the mortuary of Government Medical College Associated Hospital, Ambikapur, Sarguja, Chhattisgarh. Out of 60 cases of burns, 39 (65%) cases were females and 21 (35%) cases were males, thus indicating that majority of victims were females. Maximum number of victims 26 (43.33%) were in the age group of 21-30 years, followed by 12 (20%) were in the age group of 31-40 years. Minimum numbers of victims were in the age group of 71-80 years 01 (1.67%). Thus maximum number of cases 42 (70%) were married. Dry heat (flame) constituted 57 (95%) of cases followed by moist heat (scalds) 03 (5%) cases. Majority of victims 36 (60%) sustained more than 80% burns. In majority of cases 46 (76.67%) cause of death was septicaemia.